'Til I want no more : [large type] a novel - Pearson, Robin W. (Center Point Large Print, 2021)
"If Maxine could put her finger on the moment when her life went into a tailspin, she would point back twenty years to the day her daddy died. She tells herself he's the only person who really knew and loved her, and if he hadn't left her behind, her future would've been different. No absentee mother, no stepfather, no rebellious ripping and running as a teenager. And no JD, who gave her wandering young heart a home, at least for a time. But that's over and done. Grown-up Maxine's heart and ring finger belong to Theodore Charles, whom she'll pledge to love, honor, and obey in front of God and everybody. At least that's what she's telling people. The only folks buying it are the dog and readers of her column. Her best friend and family aren't having it - not even Celeste, the double bass-playing thirteen-year-old the community of Mount Laurel, North Carolina, believes is Maxine's adopted sister. And apparently, neither is the newly returned JD, who seems intent on toppling Maxine's reconstructed life. As her wedding day approaches, Maxine confronts what it means to be really known and loved by examining what's buried in her heart and exposing truth that's never seen the light of day"--Provided by publisher.